2019
DOI: 10.1139/cjfr-2018-0072
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for nondetection in estimating forest characteristics from single-scan terrestrial laser measurements

Abstract: A problem in the single-scan setup of terrestrial laser scanning is that some trees are shaded by others and therefore not detected in the scan. A basic estimator for forest characteristics such as tree density or basal area is based on the visible area of a scanner. However, simply compensating for nondetection by the visible area may result in considerable bias even in Poisson forests, especially if the detection of a tree depends on its size. We propose a new estimator that is a generalization of the visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…Both Liang et al [5] and Dassot et al [26], in their reviews, have underlined that several challenges still must be overcome to efficiently use TLS to replace manual field acquisition in forest mensuration. The main problem of TLS is the occluded areas, which occur using the single-scan approach, that can be reduced with a multi-scan but not completely eliminated [5,27]. Furthermore, the multi-scan approach requires more time for data acquisition and more effort in data processing [5].…”
Section: Introductionmentioning
confidence: 99%
“…Both Liang et al [5] and Dassot et al [26], in their reviews, have underlined that several challenges still must be overcome to efficiently use TLS to replace manual field acquisition in forest mensuration. The main problem of TLS is the occluded areas, which occur using the single-scan approach, that can be reduced with a multi-scan but not completely eliminated [5,27]. Furthermore, the multi-scan approach requires more time for data acquisition and more effort in data processing [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is increasing interest in making the measurements using a terrestrial laser scanner TLS or mobile laser scanner MLS , and if those are used in the field data collection, the measurement errors are no more negligible. For instance, the tree heights and diameters measured with TLS or MLS can be seriously biased [51,52] and correct inclusion probabilities of trees may be difficult to obtain [53]. If such devices become common in NFI, including the measurement errors into the uncertainty analysis becomes important.…”
Section: Measurement and Model Errorsmentioning
confidence: 99%
“…Kuronen et al (2019) improved on the work of Olofsson and Olsson (2018) by modifying the visible area based on what we call a detection condition, producing a weight for every tree that depends on its DBH and the detection condition: is the tree detected only if it is fully outside of the nonvisible area, or if the center point is visible, or if any small visible part of stem is enough for detection, or something in between, a partial visibility? The premise for the work of Kuronen et al (2019) was that the estimator of Olofsson and Olsson (2018) produced large under-and overestimation in Poisson forests when the detection condition was either full visibility or any visibility, respectively, and deduced that this was because the area from which trees could be detected in these cases was not the same as the area visible from the scanner. However, Kuronen et al (2019) also found that their estimator has a positive bias in the Poisson process case.…”
mentioning
confidence: 99%
“…The premise for the work of Kuronen et al (2019) was that the estimator of Olofsson and Olsson (2018) produced large under-and overestimation in Poisson forests when the detection condition was either full visibility or any visibility, respectively, and deduced that this was because the area from which trees could be detected in these cases was not the same as the area visible from the scanner. However, Kuronen et al (2019) also found that their estimator has a positive bias in the Poisson process case. Kansanen et al (2016) proposed estimators for stem density that correct a nondetection problem in the case of individual tree detection from airborne laser scanning (ALS) data.…”
mentioning
confidence: 99%
See 1 more Smart Citation